2020
DOI: 10.1002/app.49553
|View full text |Cite
|
Sign up to set email alerts
|

Exploring in situ integration of pongamia oil to improve barrier properties of polyurethane coatings

Abstract: Polyurethane coatings have been the focus of continuous innovation, such as bio‐based coatings and self‐healing coatings. This study investigates the route achieving superior coatings by in situ integration of pongamia oil during the curing process. Stronger urethane and carbonyl bonds for these oil‐modified coatings are observed using Fourier transform infra‐red spectroscopy. Thermogravimetric analysis reveals an increase in their thermal stability. A sustained high coating resistance and an increased Bode im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The high capacitive behaviors of the coatings, except for 0.5SPU150C, were consistent with the phase angles close to −90°. These protective barrier properties were superior to those of several PU coatings reported in the literature, which presented average | Z 5 | in the region of 10 8 Ω cm 2 for analyses at times between 14 and 30 days. In contrast, the impedance decrease for the 0.5SPU150C sample was similar to the decreases reported previously during aging. ,, This poor behavior could be attributed to the structural arrangement of the organic and inorganic parts (unhydrolyzed ethoxy groups and less dense aggregates), which facilitated access of the electrolytes to the coating/metal interface. The lower but constant | Z 5 | for the 0.5SPU183C sample could be attributed to an electrolyte path facilitated only by the PU structure, since the inorganic part presented more condensed and denser aggregates, compared to the 0.5SPU150C sample.…”
Section: Resultsmentioning
confidence: 50%
“…The high capacitive behaviors of the coatings, except for 0.5SPU150C, were consistent with the phase angles close to −90°. These protective barrier properties were superior to those of several PU coatings reported in the literature, which presented average | Z 5 | in the region of 10 8 Ω cm 2 for analyses at times between 14 and 30 days. In contrast, the impedance decrease for the 0.5SPU150C sample was similar to the decreases reported previously during aging. ,, This poor behavior could be attributed to the structural arrangement of the organic and inorganic parts (unhydrolyzed ethoxy groups and less dense aggregates), which facilitated access of the electrolytes to the coating/metal interface. The lower but constant | Z 5 | for the 0.5SPU183C sample could be attributed to an electrolyte path facilitated only by the PU structure, since the inorganic part presented more condensed and denser aggregates, compared to the 0.5SPU150C sample.…”
Section: Resultsmentioning
confidence: 50%
“…Ranade et al, indeed, investigated the effectiveness of pongamia oil as corrosion inhibitor for steel. [59] To improve the anticorrosion performances of neem oil-based PU coatings, Gite and co-workers added microcapsules containing linseed oil as a healing agent, which can be released when damages [13] Copyright 2017, Wiley-VCH.…”
Section: Bio-based Coatingsmentioning
confidence: 99%
“…A review of various PUs elucidated the influence of the crosslinking on the properties of the PUs due to the formation of the three-dimensional network. The crosslinked structure reduces the void space, pores, and free volume in the coating structure, making the path for the penetration of the corrosive electrolyte more tortuous [ 123 ]. Ahmad et al delivered a pioneering work on PU coatings prepared from LO by epoxidation and hydroxylation, showing good anticorrosive properties due to their highly crosslinked structure [ 105 ].…”
Section: Nonedible Vegetable Oil-based Polyurethane Coatingsmentioning
confidence: 99%
“…Gite et al compared the anticorrosive properties of NO-based alkyd-modified PU coatings by using an immersion method, exhibiting better anticorrosive nature due to increased crosslinking reaction [ 121 ]. Ranade et al explored the integration of PO for better crosslinking of PU coating, inhibiting electrolyte mass flow through the coating [ 123 ]. Gite et al showed that the combination of CO monoglycerides and IPDI trimer forms better crosslinked PUs, exhibiting good resistance towards acids, alkalis and solvents [ 129 ].…”
Section: Nonedible Vegetable Oil-based Polyurethane Coatingsmentioning
confidence: 99%